2020
DOI: 10.1016/j.psychres.2020.113322
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 anxiety syndrome scale: Development and psychometric properties

Abstract: Highlights A brief new measure to assess COVID-19 anxiety syndrome features is presented. The measure has acceptable levels of reliability and concurrent validity. The measure was found to predict COVID-19 anxiety and work and social adjustment controlling for other variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
228
1
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 148 publications
(250 citation statements)
references
References 31 publications
15
228
1
6
Order By: Relevance
“…Indeed, all this could have a profound effect on mental health [10]. Both the restrictive measures adopted by governments and the spread of the virus itself were associated with lower levels of life satisfaction and wellbeing [11,12] and with higher levels of anxiety [13][14][15][16], depression [17], anger [18], fear, and worry [18][19][20], resulting in fertile ground for the development of distress and chronic psychological symptoms in some people [21]. In fact, previous research has consistently identified symptoms of post-traumatic stress disorder (PTSD) [14,[22][23][24][25], which could last beyond the course of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, all this could have a profound effect on mental health [10]. Both the restrictive measures adopted by governments and the spread of the virus itself were associated with lower levels of life satisfaction and wellbeing [11,12] and with higher levels of anxiety [13][14][15][16], depression [17], anger [18], fear, and worry [18][19][20], resulting in fertile ground for the development of distress and chronic psychological symptoms in some people [21]. In fact, previous research has consistently identified symptoms of post-traumatic stress disorder (PTSD) [14,[22][23][24][25], which could last beyond the course of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Криза у области здравља проширила се и на друге домене функционисања човечанства. Ове промене су довеле и до високог нивоа стреса, повезаног са страхом, анксиозношћу и опаженом претњом (Nikčević & Spada, 2020). У нашој земљи формирани су кризни штабови, како на националном тако и на нивоу локалних заједница.…”
Section: уводunclassified
“…Када је реч о инструментима за процену психолошких аспеката суочавања са пандемијом ковида 19, међу првима је конструисана једнодимензионална Скала страха од ковида 19 (The Fear of COVID-19 Scale; Ahorsu, Lin, Imani, Saffari, Griffiths et al, 2020). Убрзо су Ли и сарадници (Lee, 2020a;Lee, 2020b;Lee, Jobe, Mathis, Gibbons, 2020;Lee, Mathis, Jobe, Pappalardo, 2020) развили Скалу анксиозности од коронавируса (Coronavirus Anxiety Scale -CAS), која се показала као валидан и користан инструмент за истраживања и практичан рад (Nikčević & Spada, 2020). Како би се сагледали шири аспекти анксиозности у време пандемије, недавно је развијена и Скала синдрома анксиозности према ковиду 19 (Nikčević & Spada, 2020).…”
Section: процена психолошких аспеката ковида 19unclassified
See 1 more Smart Citation
“…Several rating scales were developed and applied in 2020, in response to the pandemic: the fiveitem Coronavirus Anxiety Scale developed by Lee et al [5], the COVID-19-Anxiety Questionnaire modified by Petzold et al [6] based on the DSM-5 Severity Measure for Specific Phobia-Adult scale, the seven-item Fear of COVID-19 scale developed by Ahorsu et al [7], the four-item Obsession with COVID-19 Scale developed by Lee et al [8], the 11-item Coronavirus Pandemic Anxiety Scale developed by Bernardo et al [9], the two-factor nine-item COVID-19 Anxiety Syndrome Scale (6 items for perseverance and 3 items for avoidance) developed by Nikčević et al [10], and the seven-item COVID-19 Anxiety Scale developed by Silva et al [11].…”
Section: Introductionmentioning
confidence: 99%